Improving Students’ Learning Enthusiasm for the Islamic Education Subject Using Wordwall - Zulfa Ridhani Abwi; Saiful Amien; Muhammad Yusuf (research, training and philanthropy institution Natural Aceh, 2023)
The subject of Islamic Religious Education at Muhammadiyah 1 Senior High School (SMAMSA) Malang looks less attractive to students due to conventional methods and lack of learning media, which causes low enthusiasm for learning. To overcome these conditions, it is necessary to innovate learning to become more attractive, active, and not dull. This research tries to apply word wall as a learning media to increase students' learning enthusiasm. This classroom action research followed the model proposed by Kemmis et al., with two cycles, including planning, implementation, observation, and reflection. Research data were collected through observation, questionnaires, and documentation and analyzed using descriptive statistics. The results showed a significant increase in students' learning enthusiasm in class XI IPS at SMAMSA Malang. Based on the observation, results showed that the average scores of the first and second cycles were 78% and 91%. Similarly, the questionnaire results increased from 85% in cycle 1 to 90% in cycle 2. In conclusion, word walls can increase students' learning enthusiasm in class XI social studies major in Islamic Education.